The Defense-Related Isoleucic Acid Differentially Accumulates in Arabidopsis Among Branched-Chain Amino Acid-Related 2-Hydroxy Carboxylic Acids - Maksym, Rafał P.; Ghirardo, Andrea; Zhang, Wei; von Saint Paul, Veronica; Lange, Birgit; Geist, Birgit; Hajirezaei, Mohammad-Reza; Schnitzler, Jörg-Peter; Schäffner, Anton R. (Frontiers in Plant Science, 2018)
The branched-chain amino acid-related 2-hydroxy carboxylic acid isoleucic acid (ILA) enhances salicylic acid-mediated pathogen defense in Arabidopsis thaliana. ILA has been identified in A. thaliana as its glucose conjugate dependent oncorrelated with the activity of the small-molecule glucosyltransferase UGT76B1, which can glucosylate both salicylic acid and ILA in vitro. However, endogenous levels of the ILA aglycon have not yet been determined in planta. To quantify ILA as well as the related leucic acid (LA) and valic acid (VA) in plant extracts, a sensitive method based on the derivatization of small carboxylic acids by silylation and gas chromatography-mass spectrometric analysis had to bewas developed. ILA was present in all species tested including several monocotyledonous and dicotyledonous plants species as well as broadleaf and coniferous trees, whereas LA and VA were only detectable in a few species. In A. thaliana both ILA and LA were found. However, their levels varied during plant growth and in root vs. leaves. ILA levels were higher in two-week-old leaves and decreased in older plants, whereas LA exhibited a reverted accumulation pattern. Roots displayed higher ILA and LA levels compared to leaves. ILA was inversely related to UGT76B1 expression level indicating that UGT76B1 glucosylates ILA in planta. In contrast, LA was not affected by the expression of UGT76B1. To address the relation of both 2-hydroxy acids to plant defense, we studied ILA and LA levels upon infection by Pseudomonas syringae. LA abundance remained unaffected, whereas ILA was reduced. This change suggests an ILA-related attenuation of the salicylic acid response. Collectively, the branched chain amino acid-related ILA and LA differentially accumulated in Arabidopsis, supporting a specific role and regulation of the defense-modulating small-molecule ILA among these 2-hydroxy acids. The new sensitive method will pave the way to further unravel their role in plants.